2014
DOI: 10.4067/s0717-95022014000200058
|View full text |Cite
|
Sign up to set email alerts
|

Histometric Parameters of Uterus and Vagina in Breeder Female Rabbits on the Day After Weaning According to the Ordinal Number of Parturitions

Abstract: SUMMARY:The objective of this study was to establish in New Zealand female rabbits, the effect of ordinal number of parturitions on some histological parameters on the day after weaning. Tissue fragments of uterus and vagina were obtained from females of first, second and third parturitions and were processed imbedding them in paraffin in order to do histological cuts. In eight microscope fields captured by a camera connected to an optic microscope, the lumen and glandular endometrial epithelium height, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
0
0
1
Order By: Relevance
“…The anatomy and histology of the reproductive systems of rabbits according to Herrera et al (2014) and Zamora et al (2014) showed a similar morphology as the ones obtained…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 72%
“…The anatomy and histology of the reproductive systems of rabbits according to Herrera et al (2014) and Zamora et al (2014) showed a similar morphology as the ones obtained…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 72%
“…Beberapa literatur juga menyebutkan bahwa sistem reproduksi secara anatomi dan histologi berbeda-beda pada masingmasing spesies mamalia (Hafez and Hafez, 2000;Huchzermeyer et al, 2005;Rezain dan Hamedi, 2010). Menurut Skolowski et al (1973) -Herrera et al, 2014).…”
Section: Pendahuluanunclassified